The Antecedents of Communication in Buyer-Seller Relationships - Kang, Bohyeon (Indian Journal of Marketing, 2014)
Communication in buyer-seller relationships has an important role in boosting relationship performance. As a conceptual paper, this study proposes the antecedents of communication in buyer-seller relationships based on relationship marketing and transaction cost paradigms. From a literature review on relationship marketing and transaction cost literature, this study proposes the eight possible antecedents of communication - conflict, opportunism, unfairness, goal incongruity, cooperation, trust, satisfaction, and relational norms. Consequently, this study extends knowledge on how to boost communication in buyer-seller relationships. This study provides bright avenues and theoretical backgrounds for future empirical studies related to communication in buyer-seller relationships. This study provides helpful insights to academics and practitioners who are interested in understanding and utilizing communication as a tool for boosting relationship performance as well.